The Policy of Single Sex Education for Female Students in Pondok Pesantren - MUAZZA MUAZZA; NINGSIH NINGSIH; ARIE WIJAYANTI; IHSAN MAULANA PUTRA; SAMSUDIN SAMSUDIN (Ta'dib: Jurnal Pendidikan Islam, 2018)
The qualitative study with the case study approach was employed to explore and describe what kind of policies and programs of women's education made by the leaders of As'ad Foundation in Jambi City with a single sex education (SSE) learning model, especially on the implementation of curriculum policy and the provision of women educational facilities. Data were collected through interviews and documents. Participants in this study involved a leader of Pesantren and three teachers from different field of studies. Interview data were analyzed using ‘within case and cross-case analyses’ among participants. The findings showed that there were three major themes related to analysis of the educational policy of single sex educational (SSE) model in one of Pesantren As'ad in Jambi Seberang City including (1) the women’s educational policy for single sex education (SSE) model in Pesantren As'ad, (2) the women’s educational curriculum policy for single sex education (SSE) model in Pesantren As'ad, and (3) the women’s educational facility policy for single sex education (SSE) model in Pesantren As'ad.